Nanomechanics of free form and water submerged single layer graphene sheet under axial tension by using molecular dynamics simulation - Wong, C. H. (2013)
The mechanical characteristics of single layer graphene sheet are studied in this work via molecular dynamics simulation method. The effect of loading direction, size of the graphene sheet and vacancy defects in the form of slits on the mechanical performance is investigated by subjecting the graphene sheet to tensile loading at various temperatures. The findings show superior tensile characteristics of the graphene sheet loaded in zigzag direction when compared to that of the armchair direction. Furthermore, the sheet size considerably influences the mechanical characteristics of graphene under tensile loading. Our findings reveal that the temperature and the location and quantity of defects significantly impact the elastic properties of graphene. However, the variation in mechanical properties due to defects is less pronounced at higher temperatures. Additionally, we also carried out the tensile loading of graphene submerged in water for its potential applications in nano-level fluid flow. Though, the presence of surrounding water medium weakens the tensile properties, the duration of elastic limit is still exceptional that makes graphene an ideal material for applications in nano-fluidic and nano-biological devices.